1995
DOI: 10.1111/j.1439-0442.1995.tb00375.x
|View full text |Cite
|
Sign up to set email alerts
|

Abomasal Displacement in the Bovine—a Review on Character, Occurrence, Aetiology and Pathogenesis

Abstract: Summary Literature on the subject of character, history, occurrence, causes and pathogenesis of abomasal displacement in the bovine is listed and summarized. The chapter on occurrence is subdivided according to heritibility, sex, age, season, husbandry, milk yield and concomitant diseases. In the chapter on causes special consideration is given to feeding. The chapter on pathogenesis is subdivided according to mechanical influences, disturbances of the abomasal motor activity, collection of gas and dilatation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 61 publications
1
55
0
3
Order By: Relevance
“…It is reported that ketosis and fatty liver often associate with AD, and it is thought that these three disorders are interrelated (Geishauser 1995). These interrelated disorders lead to a range of metabolic activities and Correspondence to: A.K.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that ketosis and fatty liver often associate with AD, and it is thought that these three disorders are interrelated (Geishauser 1995). These interrelated disorders lead to a range of metabolic activities and Correspondence to: A.K.…”
Section: Introductionmentioning
confidence: 99%
“…Fatty liver is a frequent disease of dairy cattle occurring in early lactation (Geishauser, 1995;Bobe et al, 2004). Fatty liver is interrelated with other disease, including retained placenta, uterine infection, milk fever, left dis placement of the abomasum (LDA) and mastitis (Ing vartsen, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…DA is a multifactorial disease where the abomasum is dilated as a result of gas accumulation and dislocated to the left (LDA, left-displaced abomasum) or to the right (RDA, right-displaced abomasum and AV, abomasal volvulus) in the abdominal cavity (6). Approximately 85% of the incidences are LDA (12). Abomasal volvulus would be a rarity in LDA due to the location of the displaced abomasum.…”
Section: Introductionmentioning
confidence: 99%